The Fish Fauna of Keban Dam Lake, Elazığ, Turkey - Yıldırım, Tacettin; Şen, Dursun; Eroğlu, Mücahit; Çoban, Mehmet Zülfü; Demirol, Ferhat; Gündüz, Fatih; Canpolat, İlhan (Fırat University, 2015)
This study was done for the aim of the determining the fish fauna of Keban Dam Lake. Fish samples were collected by electroshocker, gill nets, trammel nets, cast nets from January 2008 to December 2009. A total of 28 species (Oncorhynchus mykiss, Salmo macrostigma, Acanthobrama marmid, Alburnus mossulensis, Arabibarbus grypus, Barbus lacerta, Luciobarbus subquincunciatus, Capoeta trutta, Capoeta umbla, Carassius auratus, Carassius gibelio, Chondrostoma regium, Cyprinion macrostomum, Cyprinus carpio, Garra rufa, Garra variabilis, Luciobarbus esocinus, Luciobarbus mystaceus, Luciobarbus xanthopterus, Squalius cephalus, Cobitis elazigensis, Oxynoemacheilus angorae, Oxynoemacheilus insignis, Oxynoemacheilus tigris, Mystus pelusius, Glyptothorax armeniacus, Glyptothorax kurdistanicus, Mastacembelus mastacembelus) belonging to 7 families (Salmonidae, Cyprinidae, Cobitidae, Nemacheilidae, Bagridae, Sisoridae and Mastacembelidae) were determined. Also, some morphometric and meristic characteristics of the fish samples were examined.

Bu çalışma, Keban Baraj Gölü balık faunasını tespit etmek amacıyla yapılmıştır. Balık örnekleri Ocak 2008- Aralık 2009 tarihleri arasında, elektroşoker, galsama ağları, fanyalı ağlar, serpme ağları ve kepçe yardımıyla toplanmıştır. Toplamda 7 familyaya (Salmonidae, Cyprinidae, Cobitidae, Nemacheilidae, Bagridae, Sisoridae ve Mastacembelidae) ait 28 tür (Oncorhynchus mykiss, Salmo macrostigma, Acanthobrama marmid, Alburnus mossulensis, Arabibarbus grypus, Barbus lacerta, Luciobarbus subquincunciatus, Capoeta trutta, Capoeta umbla, Carassius auratus, Carassius gibelio, Chondrostoma regium, Cyprinion macrostomum, Cyprinus carpio, Garra rufa, Garra variabilis, Luciobarbus esocinus, Luciobarbus mystaceus, Luciobarbus xanthopterus, Squalius cephalus, Cobitis elazigensis, Oxynoemacheilus angorae, Oxynoemacheilus insignis, Oxynoemacheilus tigris, Mystus pelusius, Glyptothorax armeniacus, Glyptothorax kurdistanicus, Mastacembelus mastacembelus) belirlenmiştir. Ayrıca, balık örneklerinin bazı morfometrik ve meristik özellikleri incelenmiştir.
Keban Baraj Gölü Balık Faunası, Elazığ, Türkiye